2008
DOI: 10.1348/026151007x267300
|View full text |Cite
|
Sign up to set email alerts
|

Implicit and explicit motor learning in children with and without Down's syndrome

Abstract: This paper reports a study investigating the degree of dissociation between performance shown by children with or without Down's syndrome (DS), matched on non‐verbal MA‐level, following an implicit or explicit learning procedure. Task‐specific factors were tightly controlled using the same task for both modes of learning. The implicit learning task was based on the manipulation of a graphic production principle. Our procedure trained participants to reverse the principle. In the explicit task, participants had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 61 publications
(95 reference statements)
1
11
2
1
Order By: Relevance
“…Some studies have reported that these children perform as well as typically developing children in implicit learning tasks (e.g. [63][67]). However, a number of other studies have revealed that implicit learning or memory performance is correlated with mental age [41], [68].…”
Section: Discussionmentioning
confidence: 97%
“…Some studies have reported that these children perform as well as typically developing children in implicit learning tasks (e.g. [63][67]). However, a number of other studies have revealed that implicit learning or memory performance is correlated with mental age [41], [68].…”
Section: Discussionmentioning
confidence: 97%
“…Finally, motor skill learning should be further tested in populations of atypically developing children. Children with physical and multiple disabilities and children with Down Syndrome seem to have a preference for implicit learning of handwriting (Jongbloed-Pereboom et al, 2015;Vinter & Detable, 2008) and children with intellectual disabilities increase their physical activity after implicit training of overhand throwing (Capio, Poolton, Sit, Eguia, & Masters, 2013). For learning to write, but also for learning other motor skills, studies should be undertaken to give insight in the best teaching method for atypically developing children.…”
Section: Discussionmentioning
confidence: 99%
“…In relation to set shifting, that is, the ability to mentally move back and forth between different tasks, children with ID perform on par with their MA-matched peers (Danielsson et al, 2012). For children with DS specifically, performance on tasks of shifting is poor (e.g., Contestabile, Benfenati, & Gasparini, 2010;Memisevic & Sinanovic, 2014;Vinter & Detable, 2008). Additionally, planning has been found to be significantly impaired for children with ID including children with DS (Danielsson et al, 2012;Lanfranchi et al, 2010).…”
Section: Executive Functions Cognitive Profilementioning
confidence: 99%